Organic / inorganic composite gel synergistically regulated by urea and aluminum salt and preparation method of organic / inorganic composite gel

Through the method of coordinated regulation of urea and aluminum salt, the cross-linking reaction time of polyacrylamide and phenolic substances is regulated, and the formation mineral resources are used to generate inorganic particles to form organic/inorganic composite gels, which solves the gel formation under high temperature and high salt conditions. The problem of short time improves the stability and strength of the gel and is suitable for deep oil fields to adjust and block water.

CN119463829APending Publication Date: 2025-02-18QINGDAO UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411600109.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art gel forming time is short under high temperature and high salt conditions, making it difficult to ensure that the gel liquid reaches the deep part of the formation, and the harsh conditions when preparing the composite gel are not conducive to its promotion and application.

Method used

The method of coordinated regulation of urea and aluminum salt is adopted to regulate the cross-linking reaction time of polyacrylamide and phenolic substances through the hydrolysis reaction of urea decomposition reaction and aluminum salt, and to use formation mineral resources to generate calcium carbonate particles and magnesium-aluminum layered double-layer Hydroxide particles form organic/inorganic composite gel.

Benefits of technology

The glue forming time of composite gel is extended, its stability and strength under high temperature and high salt conditions are improved, and the effective application of deep strata water blocking is achieved, and production costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463829A_ABST
    Figure CN119463829A_ABST
Patent Text Reader

Abstract

The invention discloses organic / inorganic composite gel synergistically regulated by urea and aluminum salt and a preparation method, the system can prolong the high-temperature gel forming time of a polymer, meanwhile, calcium ions are regulated and controlled to generate calcium carbonate particles, magnesium and aluminum ions are co-precipitated to generate magnesium and aluminum layered double hydroxide particles with positively charged laminates, and thus the high-temperature gel forming time of the polymer is prolonged. Organic and inorganic components form the high-elasticity-modulus composite gel through complexation, electrostatic interaction and the like. The reactant raw materials comprise a polymer main agent, a phenol cross-linking agent, an aldehyde cross-linking agent, a deoxidant, urea, an aluminum salt, a complexing agent and saline water. Under the conditions that the temperature is 95-120 DEG C, the total concentration of calcium and magnesium ions is 6817.3 mg / L and the total mineralization degree of saline water is 15.0 * 10 < 4 > mg / L, the gelling time of the composite gel can be regulated and controlled between 1.0 d and 14.9 d, and the stabilization time exceeds 135 d. The invention belongs to the field of novel materials for oilfield development, and has a wide application prospect in the field of high-strength organic / inorganic composite gel profile control and water shutoff.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the field of new materials for oilfield development, and specifically relates to an organic / inorganic composite gel synergistically regulated by urea and aluminum salt and a preparation method thereof. Background technology:

[0002] Oil is a non-renewable energy source. Achieving stable and increased crude oil production is of great strategic significance for meeting the growing energy demand, achieving sustainable economic and social development, and ensuring national energy security. However, after primary and secondary oil recovery, the crude oil recovery rate is only 20-40%. A large amount of crude oil is retained in the pores of the formation and cannot be effectively developed. Improving crude oil recovery is the core issue of oilfield production. The high water content of the output fluid of the production well is a common problem and severe challenge faced by the production of old oil fields. For example, the comprehensive water content of the output fluid of Shengli Oilfield exceeds 92%. The use of gel to adjust the water absorption profile in the injection well (i.e., profile adjustment) and to plug the water-producing layer in the production well (i.e., water plugging) has become an important measure for oil fields to improve reservoir heterogeneity and improve crude oil recovery. According to the material composition, the water gel used for oilfield profile adjustment and water plugging can be divided into inorganic gel, cross-linked polymer organic gel and organic / inorganic composite gel.

[0003] Inorganic gels are usually made of inorganic precursors such as water glass, aluminum chloride, polyaluminum chloride, etc., which are hydrolyzed and reacted with sol-gel to form silicate precipitation, silica gel, aluminum hydroxide gel or floccules. Water glass is usually sensitive to temperature, calcium and magnesium ions and pH value. It will quickly form insoluble substances under high temperature, high salt or specific pH conditions, and the gel is difficult to reach deep into the formation. Reference [Wang Ping, Dai Caili, You Qing, Zhao Guang, Meng Fanbin, Yuan Xiaohua, Research on shear-resistant and salt-resistant inorganic aluminum gel deep profile control agent, Oil and Gas Geology and Recovery, 2013, 20(6): 100-103] Inorganic aluminum hydroxide gel was prepared using aluminum chloride and urea. The system is suitable for 60-80℃ temperature conditions, and the gelation time can be adjusted in 16-824h. The system has good shear resistance and salt resistance, but the sample dehydrates significantly when the temperature is higher than 80℃. Reference [Li Zhenquan, Yuan Fuqing, Ji Yanfeng, Fan Haiming, Preparation and performance study of low-temperature inorganic aluminum gel profile control system, Journal of Xi'an Shiyou University (Natural Science Edition), 2022, 37(3): 93-99] Using aluminum chloride as reactant, hexamethylenetetramine as pH regulator, and sodium citrate as control agent, an aluminum gel plugging agent suitable for 40-60℃ low-temperature reservoir conditions was prepared. The gelling time of the plugging agent at 40℃ can be controlled within 2.5-29h, and the stability time at 60℃ can reach 60d. Improving the high-temperature stability of aluminum hydroxide gel is helpful to expand its application range. The literature [Hong He, Yefei Wang, Ziyuan Qi, Xiaojie Sun, Gelation performance and feasibility study of an environmentally friendly improved inorganic aluminum gel for conformance control under harsh reservoir conditions, Journal of Energy Resources Technology, 2017, 139, 012911] uses polyaluminum chloride and urea as reactants and sodium sulfate as a dehydration inhibitor to generate high-strength and stable aluminum hydroxide gel. The gel sample can withstand 15×10 4 mg / L NaCl, 2.5×10 4The sample can be kept stable under high mineralization conditions of 1000 mg / L CaCl2, and the stability time of the sample at 130°C can reach 120 days. However, when the temperature rises from 90°C to 130°C, the gelation time drops rapidly from 95h to 3.5h. The short gelation time under high temperature conditions makes it difficult to ensure that the gel liquid reaches the deep formation, and cannot meet the requirements of deep profile adjustment and water plugging in high-temperature formations. Patent CN108003855A discloses a single-liquid inorganic precipitation plugging agent and its preparation method, that is, the scale inhibitor is gradually diluted by formation water, and the water flow channel is blocked by gradually forming calcium carbonate particles in the formation. However, the inorganic particles formed in this study can only block low permeability layers, with a blocking rate of 54.9-64.6%, and its applicability is not explained for high permeability layers with severe heterogeneity.

[0004] Cross-linked polymer organic gels are usually three-dimensional network structures formed by polyacrylamide (PAM) and cross-linking agents. According to the type of cross-linking agent, polyacrylamide hydrogels can be divided into the following categories: ① Metal ion cross-linked polymer gels, which are partially hydrolyzed carboxylate groups in polyacrylamide and high-valent metal ions such as Al 3+ Cr 3+ 、Zr 4+The formed multi-nuclear hydroxyl bridge complex ions are cross-linked in a coordination bond manner to form a gel. This system is suitable for low temperature conditions below 80°C, because the cross-linking reaction rate of polymers and metal ions is significantly accelerated under high temperature conditions, which is not conducive to deep formation profile control. ② Phenolic cross-linked polymer gel, which is a three-dimensional network structure formed by covalent bonds in which the amide group in the polymer cross-links with organic phenolic substances. The reaction follows the nucleophilic substitution mechanism, that is, the hydroxyl group in the hydroxymethyl group is protonated to enhance the positive charge of the adjacent methylene carbon, and the nitrogen atom in the amide group attacks the carbon in the hydroxymethyl group to undergo a nucleophilic substitution reaction. Based on the above mechanism, substances that can provide protons, such as acids and ammonium salts, are often used to accelerate or promote the cross-linking reaction of phenolic and polyacrylamide. The cross-linking agents used to prepare the gel include: formaldehyde, phenol / catechol / resorcinol / hydroquinone-formaldehyde, hydroquinone / resorcinol-hexamethylenetetramine, melamine-formaldehyde, etc. The gelation time of this system is significantly longer than that of the metal ion cross-linking system, and the temperature and salt resistance of the product are improved. ③ Polyethyleneimine (PEI) cross-linked organic gel. PEI is a low-toxic and environmentally friendly material that can undergo cross-linking reactions with polymers such as polyacrylamide and poly(acrylamide-tert-butyl acrylate) to prepare hydrogels. In the cross-linking reaction, the imino nitrogen of PEI attacks the carbonyl carbon of polyacrylamide through a nucleophilic reaction, completes the transamidation reaction and forms a covalent bond. This system has low pollution, but the high concentration of reaction components leads to high gel cost, and the system has weak salt tolerance. The common problem of polyacrylamide organic gel is that the polymer cross-linking reaction is fast at high temperature. Under high salt conditions, the amide group hydrolyzes and combines with calcium and magnesium ions in the brine through electrostatic action, resulting in excessive cross-linking of the gel and dehydration, and the gel stability decreases. Prolonging the gelation time of polyacrylamide and enhancing the strength and stability of the gel under high temperature and high salt conditions are technical problems that need to be solved urgently in oilfield profile control and water plugging.

[0005] Organic / inorganic composite gel is a new type of gel system constructed by cross-linked polyacrylamide and inorganic nanoparticles, which is increasingly attracting people's attention. Organic and inorganic components enhance the strength and stability of composite gels through hydrogen bonds, electrostatic effects or van der Waals forces, and inorganic particles can also form physical crosslinking points with polymer molecules. Composite gels have higher elastic modulus and significantly enhanced temperature and salt resistance, and have become a new research direction in this field. The inorganic nanoparticles introduced in the preparation of composite gels include: silica, alumina, magnesium oxide, fly ash, montmorillonite, laponite, layered double hydroxides, graphene oxide, graphene, multi-walled carbon nanotubes and carbonate particles.

[0006] The literature [Yifei Liu, Caili Dai, Kai Wang, Chenwei Zou, Mingwei Gao, Yanchao Fang, Mingwei Zhao, Yining Wu, Qing You, Study on a novel cross-linked polymer gel strengthened with silica nanoparticles, Energy Fuels, 2017, 31, 9152-9161] reported the preparation of polyacrylamide gel using hydroquinone-hexamethylenetetramine as a crosslinking agent, in which nano-SiO2 particles were added to form an organic / inorganic composite gel. The experimental results show that when the concentration of nano-SiO2 is 0.1-0.3wt%, the elastic modulus and strength of the system are significantly increased. However, as the concentration of SiO2 particles increases, the gelation time of the composite gel decreases from 16h to 9h, which is not conducive to deep profile control and water plugging operations in oil fields. Patent CN112980412A discloses a displacement agent suitable for high-temperature and high-salt heavy oil reservoirs and a preparation method thereof. The system uses silica sol, silica-alumina sol and aluminum sol as stabilizers to enhance the stability of gel formed by acrylamide / 2-acrylamide-2-methylpropane sulfonic acid, acrylamide / N-vinyl pyrrolidone / 2-acrylamide-2-methylpropane sulfonic acid copolymer and phenolic crosslinker. The system can be used in a total mineralization of 22×10 4 The composite gel can gel under the conditions of 100 mg / L and 130°C and has good long-term stability. However, the gelation time of the composite gel is only 7-15h, and the short gelation time cannot ensure that the gel liquid reaches the deep reservoir. Patent CN108587585A uses salt-thickening or temperature-thickening amphiphilic polymers, crosslinking agents, surfactants and inorganic particles (1-50nm) to construct organic / inorganic composite gel and use it as a profile control and water plugging agent. When the total mineralization of formation water is 8.5×10 4 The dehydration rate is 6.0-7.5% under the conditions of 100 mg / L and 85°C for 30 days, but the gelation time range shown in the examples is only 3.2-4.5 hours. The short gelation time at high temperature is a common problem of the above composite gels.

[0007] Patent CN102516961A discloses an organic-inorganic composite cross-linking plugging agent suitable for high-temperature oil reservoirs. The system uses polyacrylamide, organic cross-linking agent and water glass to construct a composite gel, which is suitable for 90-140℃ formation profile control and water plugging. It is aged at 130℃ for 90 days without dehydration, but the system needs to use fresh water to prepare samples, and does not explain its applicability to high-mineralization formations. Patent CN109679604B and Patent CN111808585A respectively disclose a salt-resistant and high-temperature resistant hydrogel and its preparation method and application, a slow-crosslinking temperature-resistant and salt-resistant high-strength gel and its preparation method and application. They respectively use hydrochloric acid generated by hydrolysis of weak acids (such as acetic acid, etc.) and organic acids (such as chloroacetic acid, etc.) to regulate the cross-linking reaction of polyvinyl alcohol and aldehyde substances, and use nano-silica as a stabilizer to prepare organic / inorganic composite gels, which can be used for 130℃ and formation water with a total mineralization of 22×10 4 mg / L water injection well profile control, but both systems require the use of fresh water to prepare the gel liquid, and their gelation times are 1-2h and 1.5-22h respectively. Although the gelation time of the latter system is extended, it is still relatively short compared to the requirements of deep oil field profile control and water plugging construction, and the use of fresh water to prepare the gel sample also increases the production cost.

[0008] The literature [Reihaneh Zolfaghari, Ali A. Katbab, Javad Nabavizadeh, Ramin Yousefzadeh Tabasi, Majid Hossein Nejad, Preparation and characterization of nanocomposite hydrogels based on polyacrylamide for enhanced oil recovery applications, Journal of Applied Polymer Science, 2006, 100, 2096-2103] prepared partially hydrolyzed polyacrylamide (HPAM) / montmorillonite composite gel. The polymer in this system can intercalate and exfoliate inorganic minerals, the interaction between organic-inorganic components is enhanced, and the thermal stability of the composite gel is significantly improved. The literature [Paul Tongwa, Runar Nygaard, Baojun Bai, Evaluation of a nanocomposite hydrogel for water shut-off in enhanced oil recovery applications: design, synthesis, and characterization, Journal of Applied Polymer Science, 2013, 128, 1, 787-794] uses lithium soapstone nanosheets as a physical crosslinker to form a composite gel with HPAM. Among them, the amide group forms a hydrogen bond with the surface of the clay particles, and the carboxylate anions and the metal cations at the edge of the clay particles have an electrostatic effect, which greatly improves the mechanical properties and thermal stability of the composite gel. The literature [Ziqiao Hu, Guangming Chen, Aqueous dispersions of layered double hydroxide / polyacrylamide nanocomposites: preparation and rheology, Journal of Materials Chemistry A, 2014, 2, 13593-13601] first peeled positively charged magnesium aluminum layered double hydroxides (LDHs) in water, then added acrylamide monomer and initiator to form PAM / LDHs composite hydrogel for in-situ polymerization. The composite exhibited excellent mechanical toughness.The literature [Hai-Peng Zhang, Jing-Jing Cao, Wen-Bing Jiang, Yu-Qi Yang, Bo-Yuan Zhu, Xiao-Yu Liu, Yang Wu, Xin Sun, Ariane Felicite Bibiche Essouma Essouma, Jian Liu, Ting-Yan Xing, Synthesis and mechanical properties of polyacrylamide gel doped with graphene oxide, Energies, 2022, 15, 5714] studied the characteristics of composite gels formed in PAM / PEI gel system with graphene oxide (GO). The results showed that with the increase of GO content (0-0.2wt%), the gelation time was extended from 50h to 105h, the dehydration temperature of the composite gel gradually increased, and the stability was enhanced. However, the elastic modulus of the composite gel is smaller than that of the pure organic gel, indicating that the performance of the system needs to be improved.

[0009] Patent CN105586024A discloses a plugging agent and a method for high-temperature and high-mineralization oil reservoir profile control and water plugging. The system uses hydrolyzed polyacrylamide as the main agent, phenolic substances as cross-linking agents, sodium carbonate as an inorganic particle inducer, and water containing high concentrations of calcium ions to prepare an organic / inorganic composite gel. The gel formed by the polymer and the cross-linking agent has a certain salt resistance, and the inducer can react with calcium ions to form inorganic particles, which has high temperature resistance. The prepared organic / inorganic composite gel can be used as a plugging agent for 80-120°C and a total mineralization of 8.5×10 4 mg / L, Ca 2+ Concentration 1.2×10 4 Under the condition of 100 mg / L, the composite gel was stable at 120°C for 60 days without dehydration, and had high plugging strength and long-term stability. However, the patent did not explain the gelation time of the composite gel and how to control the gelation time. In addition, when sodium carbonate encounters high concentration of calcium ions, it will precipitate quickly in the system and easily form insoluble substances near the wellbore, which is not conducive to the injection of gel liquid and reaching the deep part of the reservoir to implement profile control and water plugging.

[0010] In summary, the strength and stability of organic / inorganic composite gels are significantly enhanced under high temperature and high salt conditions, but the short gelation time under high temperature conditions limits the gel liquid from reaching the deep formation; the inorganic particles added when preparing composite gels often need to regulate their particle size, sheet thickness, concentration, surface properties, etc., and the harsh preparation conditions are not conducive to the promotion and application of composite gels; in terms of the regulation of the action mode of organic and inorganic components, the existing research systems mostly involve coordination and hydrogen bonds, while the direct use of the electrostatic interaction between the positively charged LDHs particles in the layer and the carboxylates produced by the hydrolysis of polyacrylamide to construct high-strength organic / inorganic composite gels is still a blank. Formation brine contains abundant calcium and magnesium ions, which are important factors that cause the stability of polyacrylamide gels to decrease under high temperature and high salt conditions. At the same time, these high-valent metal ions are also potential valuable resources for the preparation of inorganic nanoparticles. The use of urea and aluminum salts to synergistically regulate the high-temperature cross-linking reaction time of composite gels, the action type of organic-inorganic components, the strength and stability of composite gels, and the use of formation mineral resources to prepare organic / inorganic composite gels in situ is of great significance in the field of chemical profile control and water plugging in oil fields. Summary of the invention:

[0011] The purpose of the present invention is to provide an organic / inorganic composite gel synergistically regulated by urea and aluminum salt and a preparation method thereof in view of the deficiencies in the prior art, wherein the urea decomposition reaction and the aluminum salt hydrolysis reaction are used to regulate the crosslinking reaction time of polyacrylamide and phenolic substances and the precipitation reaction of calcium, magnesium and aluminum ions, and calcium carbonate particles and magnesium-aluminum layered double hydroxide particles with positive layer plates are generated in situ and form an organic / inorganic composite gel with phenolic crosslinked polyacrylamide.

[0012] To achieve the above purpose, the organic / inorganic composite gel synergistically regulated by urea and aluminum salt provided by the present invention is prepared from the following components in mass percentage: 0.50%-2.00% of a polymer main agent, 0.05%-0.80% of a phenolic cross-linking agent, 0.05%-0.80% of an aldehyde cross-linking agent, 0.01%-0.10% of an oxygen scavenger, 1.50%-4.00% of urea, 0.10%-0.80% of an aluminum salt, 0.20%-1.20% of a complexing agent, and the remainder being brine.

[0013] The main polymer is polyacrylamide, including at least one of nonionic polyacrylamide, partially hydrolyzed polyacrylamide and acrylamide copolymer, and the preferred polymer is nonionic polyacrylamide; the relative molecular weight of the polymer is 1 million to 5 million; the phenolic crosslinking agent includes at least one of phenol, resorcinol and hydroquinone, and the preferred phenolic crosslinking agent is hydroquinone; the aldehyde crosslinking agent is at least one of formaldehyde or polyformaldehyde; the brine is simulated high-mineralization formation water, and the total mineralization of the high-mineralization brine is 15.0×10 4mg / L, the total concentration of calcium and magnesium ions is 6817.3 mg / L; in the organic / inorganic composite gel, thiourea is a scavenger for enhancing the stability of the composite gel under high temperature conditions; the aluminum salt includes at least one of aluminum chloride, aluminum sulfate, aluminum nitrate, and aluminum citrate, and the preferred aluminum salt is aluminum chloride; the complexing agent is at least one of sodium citrate and disodium ethylenediaminetetraacetic acid, and the preferred complexing agent is sodium citrate.

[0014] The organic component in the composite gel is a gel formed by polyacrylamide and a phenolic crosslinker, and the inorganic components include calcium carbonate particles and magnesium-aluminum layered double hydroxide particles with positively charged layers. The layered double hydroxide and the organic component carboxylate significantly improve the elastic modulus of the composite gel through electrostatic interaction.

[0015] The gelling time of the composite gel reaction solution can be controlled within 1.0-14.9 days at 95-120°C, and the formed gel has a stability time of more than 135 days. The composite gel is suitable for use as a profile control and water plugging agent in deep high-temperature and high-salinity reservoirs.

[0016] Another object of the present invention is to provide a method for preparing an organic / inorganic composite gel synergistically regulated by urea and aluminum salt, comprising the following steps: adding a polymer to a saline solution, stirring until completely dissolved, to obtain a polymer saline solution; adding an aluminum salt and a complexing agent to the polymer saline solution, stirring until completely dissolved, to obtain a polymer saline solution containing aluminum salt; adding a phenolic crosslinking agent to the polymer saline solution containing aluminum salt, stirring until completely dissolved, to obtain a polymer saline solution containing phenolic substances; continuing to add an aldehyde crosslinking agent, a deoxidizer and urea to the polymer saline solution containing phenolic substances, stirring evenly, to obtain a composite gel reaction solution; placing the composite gel reaction solution at a constant temperature of 95-120° C. for aging, to obtain a composite gel.

[0017] The method for preparing the organic / inorganic composite gel also includes the following control mechanism: urea decomposes to produce ammonia and carbon dioxide, and hydroxide and carbonate anions are generated in the aqueous solution thereof, which can delay the cross-linking reaction between polyacrylamide and hydroxymethylphenol according to the nucleophilic substitution mechanism; the hydrolysis of aluminum ions promotes the generation of hydrogen ions, which is helpful for the nucleophilic substitution reaction between polyacrylamide and phenolic cross-linking agent, that is, it accelerates the cross-linking reaction; under the dual control of urea and aluminum salt, when the mass percentage of urea in the reaction system is controlled within the range of 1.50%-4.00% at 95-120°C, the gelation time of the reaction solution can be controlled within the range of 1.0-14.9d, and increasing the urea concentration in the reaction system can prolong the gelation time of the reaction solution.

[0018] The method for preparing the organic / inorganic composite gel also includes the following control mechanism: urea decomposes to produce ammonia and carbon dioxide, and hydroxide and carbonate anions are generated in the aqueous solution. Calcium and magnesium ions in the formation water and aluminum ions added to the solution can react with the anions to generate inorganic particles, and an organic / inorganic composite gel containing calcium carbonate particles and magnesium-aluminum layered double hydroxide inorganic particles is prepared in situ. The layered double hydroxide and the organic component carboxylate significantly improve the elastic modulus of the composite gel through electrostatic interaction.

[0019] The method for preparing the organic / inorganic composite gel also includes the following features: it can convert calcium and magnesium ions that destroy the stability of the gel into calcium carbonate and magnesium aluminum double metal hydroxide inorganic particles, thereby improving the elastic modulus, strength and stability of the composite gel, achieving comprehensive utilization of stratum mineral resources and transforming unfavorable factors into favorable conditions.

[0020] The beneficial effects of the present invention are as follows: urea and aluminum salt can be used to coordinately regulate the gelation time, elastic modulus and strength of composite gel, regulate the types and interactions of organic and inorganic components, and comprehensively utilize polymer brine solution to prepare organic / inorganic composite gel in situ. First, when urea decomposes, hydroxide ions and carbonate ions will be generated in the solution, which can effectively delay the cross-linking reaction between polyacrylamide and phenolic substances through the nucleophilic substitution mechanism. Increasing the urea concentration in the reaction system can easily achieve the purpose of delaying the cross-linking reaction of polyacrylamide, breaking through the technical bottleneck of short polymer cross-linking reaction time under high temperature conditions, and providing a strong guarantee for the migration of gel reaction liquid to deep formations. Second, this patent is based on the conversion of calcium ions into calcium carbonate particles through the urea decomposition reaction, and urea and aluminum salt regulate the magnesium-aluminum co-precipitation reaction to generate magnesium-aluminum layered double hydroxide particles with positive charges in the layer plates, thereby weakening or reducing the adverse effects of high-valent metal ions on the stability of polymer gels. Third, the generated inorganic particles and organic polymer gel form an organic / inorganic composite gel through coordination and electrostatic effects, especially the positively charged magnesium-aluminum layered double hydroxide in the layer plate and the carboxylate anions in the polymer gel have electrostatic effects, which further improve the elastic modulus of the composite gel. The process of generating the composite gel realizes the perfect combination of inorganic salt treatment and application in formation water, especially the comprehensive utilization of inorganic salts in formation water as mineral resources, which improves the strength and stability of the composite gel. The prepared composite gel has the characteristics of long and controllable gelation time and good stability, and has broad application prospects in the field of deep profile control and water plugging in high-temperature and high-salt oil reservoirs. Fourth, in terms of the preparation method, this patent provides a new method for in-situ preparation of organic / inorganic composite gel by comprehensive utilization of polymer brine solution, without the need for additional inorganic particles, low cost and simple method. Description of the drawings:

[0021] The following drawings are provided to illustrate and explain the present invention, but are not intended to limit the scope of the present invention.

[0022] Figure 1 is the XRD pattern of inorganic particles;

[0023] Figure 2 Scanning electron micrographs of organic / inorganic composite gel samples synergistically regulated by urea and aluminum salt, a sample containing salt without water washing, b sample containing no salt after water washing;

[0024] Figure 3 This is the relationship diagram between the elastic modulus G' and oscillation frequency of different gel samples. Specific implementation method:

[0025] The present invention is described in detail below in conjunction with embodiments. It should be pointed out that the embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0026] In the embodiment, the strength of the gel sample and the corresponding gelation time and stability time are recorded by referring to the GSC (Gel Strength Codes) visual code evaluation method proposed by Sydansk et al. The specific operation is: take 20mL of gel reaction solution (liquid mixture before gelation) and seal it in an ampoule bottle and place it in a constant temperature box for heating. The time when the gel sample reaches the strength code D is taken as the gelation time, and the sample stability time is the time when the gel is dehydrated by 5mL and the dehydration rate (i.e., dehydrated volume / initial volume of gel sample × 100%) reaches 25%. The classification of gel strength grades is shown in Table 1.

[0027] The relative molecular weight of the nonionic polyacrylamide used in the embodiment is 1.4 million, and the degree of hydrolysis is 1.3%. The polymer is provided in the form of a mother liquor with a mass percentage of 5%. Phenol, resorcinol, hydroquinone, and formaldehyde (mass percentage 37%) are all analytical reagents. The salt mother liquor is prepared using NaCl, CaCl2, MgCl2·6H2O and deionized water, wherein the molar ratio of metal ions is n Na+ ∶n Ca2+ ∶n Mg2+ =25.52:1.00:1.65, the total mineralization of the brine mother liquor is 30×10 4 mg / L. Weigh 127.17 g, 9.46 g, and 28.52 g of NaCl, CaCl2, and MgCl2·6H2O, respectively, and dissolve them in deionized water to prepare 500 mL of brine mother liquor with a total mineralization of 30×10 4 mg / L,Na + , Ca 2+ and Mg 2+The concentrations of 99998.7 mg / L, 6816.0 mg / L and 6818.6 mg / L were respectively. When preparing the gel reaction solution, a certain volume of polymer mother solution, salt mother solution and deionized water were added according to the designed concentration, and the mineralization degree of the polymer salt solution was adjusted to 15×10 4 mg / L, the total concentration of calcium and magnesium ions is 6817.3 mg / L.

[0028] Table 1. Gel strength classification table

[0029]

[0030] Embodiment 1:

[0031] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 mg / L polyacrylamide salt solution; add 0.0748g AlCl3·H2O and 0.0911g sodium citrate (C6H5Na3O7·2H2O) to the above solution respectively, and stir until the sample is dissolved; add 0.0793g hydroquinone to the solution under stirring conditions, stir until it is completely dissolved, and measure 213μL of 37% formaldehyde solution, 0.0200g thiourea, and 0.5522g urea to add to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at 95℃ to generate a composite gel. The reaction solution gelation time is 6.9d, and the gel sample stability time exceeds 135d. At the 135th day, the sample strength symbol is I.

[0032] Embodiment 2:

[0033] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4mg / L polyacrylamide salt solution; add 0.0748g AlCl3·H2O and 0.0911g sodium citrate (C6H5Na3O7·2H2O) to the above solution respectively, and stir until the sample is dissolved; add 0.0793g hydroquinone to the solution under stirring conditions, stir until it is completely dissolved, and measure 213μL of 37% formaldehyde solution, 0.0200g thiourea, and 1.1044g urea to add to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at a constant temperature of 95℃ to generate a composite gel. The reaction solution gelation time is 14.9d, and the gel sample stability time exceeds 135d. At the 135th day, the sample strength symbol is I.

[0034] Embodiment 3:

[0035] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 mg / L polyacrylamide salt solution; add 0.0748g AlCl3·H2O and 0.0911g sodium citrate (C6H5Na3O7·2H2O) to the above solution respectively, and stir until the sample is dissolved; add 0.0620g hydroquinone to the solution under stirring conditions, stir until it is completely dissolved, and measure 167μL of 37% formaldehyde solution, 0.0200g thiourea, and 1.1044g urea to add to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at a constant temperature of 120℃ to generate a composite gel. The reaction solution gelation time is 6.9d, and the gel sample stability time exceeds 135d. At the 135th day, the sample strength symbol is I.

[0036] Embodiment 4:

[0037] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4mg / L polyacrylamide salt solution; add 0.1495g AlCl3·H2O and 0.1821g sodium citrate (C6H5Na3O7·2H2O) to the above solution respectively, and stir until the sample is dissolved; add 0.0793g hydroquinone to the solution under stirring conditions, stir until it is completely dissolved, and measure 213μL of 37% formaldehyde solution, 0.0200g thiourea, and 0.5624g urea to add to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at 95℃ to generate a composite gel. The reaction solution gelation time is 5.7d, and the gel sample stability time exceeds 135d. At the 135th day, the sample strength symbol is I.

[0038] Comparative Example 1:

[0039] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 mg / L polyacrylamide salt solution; add 0.1495g AlCl3·H2O to the above solution and stir until the sample is dissolved; add 0.0793g hydroquinone to the solution under stirring conditions and stir until it is completely dissolved, and measure 213μL of 37% formaldehyde solution, 0.0200g thiourea, and 0.5624g urea respectively and add them to the above solution and stir evenly to obtain a composite gel reaction solution without a complexing agent. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at 95℃ to generate a composite gel. The reaction solution gelation time is 4.4d, and the gel sample stability time exceeds 135d. At the 135th day, the sample strength symbol is I.

[0040] The difference between Comparative Example 1 and Example 4 is that the complexing agent sodium citrate is not added in Comparative Example 1, and the other sample compositions are the same. The experimental results show that the gelling time of the gel reaction liquid is shortened when the complexing agent is not added. This is because the hydrolysis of aluminum ions will lead to the formation of hydrogen ions, which will promote the nucleophilic substitution cross-linking reaction between the amide group and the hydroxymethyl group. The experimental results show that the complexing agent has the effect of delaying the cross-linking reaction after complexing aluminum ions. The complexing agent has no obvious effect on the strength and stability of the organic / inorganic composite gel.

[0041] Comparative Example 2:

[0042] Weigh 0.3796g CaCl2, 1.1409g MgCl2·6H2O, 0.1495g AlCl3·H2O and 0.1821g sodium citrate (C6H5Na3O7·2H2O), 0.0200g thiourea and 0.5624g urea respectively, dissolve them in deionized water to prepare 40mL inorganic reaction solution. The solution has the same concentration of calcium salt, magnesium salt, aluminum salt, complexing agent and urea as the composite gel reaction solution of Example 4 of the present invention. Seal the above solution in a glass bottle with a lid and age it at a constant temperature of 95°C for 30 days to ensure that the inorganic ions therein are fully precipitated. Then take out the glass bottle, wash the precipitated sample with deionized water to remove unreacted electrolyte, dry the obtained precipitate at 95°C, grind it and perform XRD test on the sample. The XRD curve of the obtained sample is as shown below: Figure 1 As shown. By comparing with the standard sample card, it can be confirmed that the inorganic precipitation structure generated in this comparative example 2 includes MgAl-LDHs particles and CaCO3 particles. Since the concentrations of calcium, magnesium and aluminum ions in comparative example 2 and embodiment 4 are the same, the composition of inorganic particles in the comparative example 2 sample is the same as that in embodiment 4. This comparative example indirectly confirms the structural characteristics and composition of the inorganic particles in embodiment 4, that is, the inorganic components contained in embodiment 4 are MgAl-LDHs particles and CaCO3 particles.

[0043] Embodiment 5:

[0044] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 mg / L polyacrylamide salt solution; add 0.1495g AlCl3·H2O and 0.1821g sodium citrate (C6H5Na3O7·2H2O) to the salt solution respectively, and stir until the sample is dissolved; add 0.0793g hydroquinone to the solution under stirring conditions, stir until it is completely dissolved, and measure 213μL of 37% formaldehyde solution, 0.0200g thiourea, and 1.1249g urea to add to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at 95℃ to generate a composite gel. The reaction solution gelation time is 12.4d, and the gel sample stability time exceeds 135d. At the 135th day, the sample strength symbol is I.

[0045] Embodiment 6:

[0046] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 mg / L polyacrylamide salt solution; add 0.1495g AlCl3·H2O and 0.1821g sodium citrate (C6H5Na3O7·2H2O) to the salt solution, respectively, and stir until the sample is dissolved; add 0.0620g hydroquinone to the solution under stirring conditions, stir until it is completely dissolved, and measure 167μL of 37% formaldehyde solution, 0.0200g thiourea, and 1.1249g urea to add to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at a constant temperature of 120℃ to generate a composite gel. The reaction solution gelation time is 7.5d, and the gel sample stability time exceeds 135d. At the 135th day, the sample strength symbol is H.

[0047] Embodiment 7:

[0048] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 mg / L polyacrylamide salt solution; add 0.2242g AlCl3·H2O and 0.2731g sodium citrate (C6H5Na3O7·2H2O) to the salt solution respectively, and stir until the sample is dissolved; add 0.0793g hydroquinone to the solution under stirring conditions, stir until it is completely dissolved, and measure 213μL of 37% formaldehyde solution, 0.0200g thiourea, and 0.5727g urea to add to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at 95℃ to generate a composite gel. The reaction solution gelation time is 4.6d, and the gel sample stability time exceeds 135d. At the 135th day, the sample strength symbol is I.

[0049] Figure 2 This is a scanning electron micrograph of the organic / inorganic composite gel prepared in Example 7, wherein: Figure 2 a. Figure 2b corresponds to the unwashed salt-containing sample and the washed salt-free sample. As can be seen from the figure, the composite gel has a typical three-dimensional network structure. The composite gel liquid phase contains a large amount of sodium chloride inorganic salt. During the evaporation of the solvent to dry the gel sample, the inorganic salt precipitates from the solvent and deposits on the polymer surface, such as Figure 2 As shown in Fig. a, this surface deposition structure has little significance for enhancing the strength and stability of the composite gel. In order to specifically observe the distribution of organic and inorganic components in the composite gel, the inventors also repeatedly washed the gel sample with water to remove the soluble inorganic salts, and then freeze-dried it to observe the morphological characteristics of the complex formed by the inorganic insoluble matter and the organic gel component, as shown in Fig. Figure 2 b. After washing away the soluble inorganic salts, there are still many particles attached to the surface of the polymer gel. These should be the insoluble substances formed by calcium, magnesium and aluminum salts under experimental conditions, including large-sized magnesium-aluminum layered double hydroxides (about 2 μm in diameter) and small-sized calcium carbonate particles (about 200 nm in diameter). The particles are embedded or wrapped in the polymer gel network. The inorganic particles are compounded with the cross-linked polymer gel network, which helps to improve the elastic modulus and structural strength of the composite gel.

[0050] Embodiment 8:

[0051] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 mg / L polyacrylamide salt solution; add 0.2242g AlCl3·H2O and 0.2731g sodium citrate (C6H5Na3O7·2H2O) to the salt solution respectively, and stir until the sample is dissolved; add 0.0793g hydroquinone to the solution under stirring conditions, stir until it is completely dissolved, and measure 213μL of 37% formaldehyde solution, 0.0200g thiourea, and 1.1454g urea to add to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at 95℃ to generate a composite gel. The reaction solution gelation time is 12.9d, and the gel sample stability time exceeds 135d. At the 135th day, the sample strength symbol is I.

[0052] Embodiment 9:

[0053] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 mg / L polyacrylamide salt solution; add 0.2242g AlCl3·H2O and 0.2731g sodium citrate (C6H5Na3O7·2H2O) to the salt solution respectively, and stir until the sample is dissolved; add 0.0620g hydroquinone to the solution under stirring conditions, stir until it is completely dissolved, and measure 167μL of 37% formaldehyde solution, 0.0200g thiourea, and 1.1454g urea to add to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at 120℃ to generate a composite gel. The reaction solution gelation time is 8.1d, and the gel sample stability time exceeds 135d. At the 135th day, the sample strength symbol is F.

[0054] Embodiment 10:

[0055] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 mg / L polyacrylamide salt solution; add 0.2990g AlCl3·H2O and 0.3641g sodium citrate (C6H5Na3O7·2H2O) to the salt solution, respectively, and stir until the sample is dissolved; add 0.0793g hydroquinone to the solution under stirring conditions, stir until it is completely dissolved, and measure 213μL of 37% formaldehyde solution, 0.0200g thiourea, and 0.5830g urea to add to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at 95℃ to generate a composite gel. The reaction solution gelation time is 1.0d, and the gel sample stability time exceeds 146d. At the 146th day, the sample strength symbol is G.

[0056] Embodiment 11:

[0057] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×104 mg / L polyacrylamide salt solution; add 0.2990g AlCl3·H2O and 0.3641g sodium citrate (C6H5Na3O7·2H2O) to the salt solution respectively, and stir until the sample is dissolved; add 0.0793g hydroquinone to the solution under stirring conditions, stir until it is completely dissolved, and measure 213μL of 37% formaldehyde solution, 0.0200g thiourea, and 0.7287g urea to add to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at 95℃ to generate a composite gel. The reaction solution gelation time is 1.1d, and the gel sample stability time exceeds 135d. At the 135th day, the sample strength symbol is I.

[0058] Embodiment 12:

[0059] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 mg / L polyacrylamide salt solution; add 0.2990g AlCl3·H2O and 0.3641g sodium citrate (C6H5Na3O7·2H2O) to the salt solution respectively, and stir until the sample is dissolved; add 0.0793g hydroquinone to the solution under stirring conditions, stir until it is completely dissolved, and measure 213μL of 37% formaldehyde solution, 0.0200g thiourea, and 1.1659g urea to add to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at 95℃ to generate a composite gel. The reaction solution gelation time is 3.4d, and the gel sample stability time exceeds 135d. At the 135th day, the sample strength symbol is I.

[0060] Embodiment 13:

[0061] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4mg / L polyacrylamide salt solution; add 0.2990g AlCl3·H2O and 0.3641g sodium citrate (C6H5Na3O7·2H2O) to the above salt solution, respectively, and stir until the sample is dissolved; add 0.0620g hydroquinone to the solution under stirring conditions, stir until completely dissolved, and measure 167μL of 37% formaldehyde solution, 0.0200g thiourea, and 0.5830g urea to add to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at a constant temperature of 120℃ to generate a composite gel. The gelation time of the reaction solution is 2.9d, and the stability time of the gel sample exceeds 141d. At the 141st day, the sample strength symbol is I. The sample is an organic / inorganic composite gel sample synergistically regulated by urea (U) and aluminum salt (Al), wherein the mineralization degree (T) of the inorganic salt is 15×10 4 mg / L, the mass percentage concentrations of urea and aluminum chloride are 1.31% and 0.37% respectively, so the sample symbol is named composite-T15-U1.31-Al0.37.

[0062] Comparative Example 3:

[0063] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 0.0620g hydroquinone was added to the solution of 100 mg / L polyacrylamide salt solution under stirring, and stirred until completely dissolved. 167μL of 37% formaldehyde solution, 0.0200g thiourea, and 0.5419g urea were added to the above solution and stirred evenly to obtain the urea-regulated composite gel reaction solution. 20mL of the reaction solution sample was encapsulated in an ampoule bottle and aged at 120℃ to generate a composite gel. The gelation time of the reaction solution was 2.9d, and the stability time of the gel sample exceeded 141d. At the 141st day, the sample strength symbol was H. This sample is an organic / inorganic composite gel sample regulated by urea (U), in which the mineralization degree (T) of the inorganic salt is 15×10 4 mg / L, the mass percentage concentration of urea is 1.34%, so the sample symbol is named Composite-T15-U1.34.

[0064] Comparative Example 3 is an organic / inorganic composite gel regulated by pure urea, and Example 13 is an organic / inorganic composite gel regulated by urea and aluminum salt; the polymer, crosslinking agent, and salt water used to prepare the samples in these two systems are the same. Their gelation time at 120°C is 2.9 days. After the samples have been aged for 7.3 days, both samples have formed composite gels. Their elastic moduli are tested in the oscillation frequency range of 0.01-10 Hz, as shown in FIG. Figure 3 As shown. The elastic modulus of Comparative Example 3 is 40-50Pa, while the elastic modulus of Example 13 is about 43-76Pa, that is, the viscous modulus and strength of the composite gel synergistically regulated by urea and aluminum salt are greater. In addition, the elastic modulus of the obtained gel samples is much greater than the viscous modulus, indicating that the gel samples have good solid-like properties and viscoelasticity.

[0065] Embodiment 14:

[0066] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed, and 8 mL of 5% non-ionic polyacrylamide mother solution was added to the solution. The sample was stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 mg / L polyacrylamide salt solution; add 0.2990g AlCl3·H2O and 0.3641g sodium citrate (C6H5Na3O7·2H2O) to the above salt solution, respectively, and stir until the sample is dissolved; add 0.0620g hydroquinone to the solution under stirring conditions, stir until completely dissolved, and measure 167μL of 37% formaldehyde solution, 0.0200g thiourea, and 0.7287g urea to the above solution and stir evenly to obtain the composite gel reaction solution of the present invention. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at a constant temperature of 120℃ to generate a composite gel. The gelation time of the reaction solution is 3.0d, and the stability time of the gel sample exceeds 141d. At the 141st day, the sample strength symbol is I. The sample is an organic / inorganic composite gel sample synergistically regulated by urea (U) and aluminum salt (Al), wherein the mineralization degree (T) of the inorganic salt is 15×10 4 mg / L, the mass percentage concentrations of urea and aluminum chloride are 1.63% and 0.37% respectively, so the sample symbol is named composite-T15-U1.63-Al0.37.

[0067] Comparative Example 4:

[0068] In a 100 mL beaker, 20 mL of salt mother solution and 12 mL of deionized water were measured and mixed evenly; 8 mL of 5% nonionic polyacrylamide mother solution was added to the solution, and the sample was stirred at 500 rpm for 0.5 h to make the sample uniform, thus obtaining a polymer with a mass percentage of 1% and a mineralization degree of 15×10 4 mg / L polyacrylamide salt solution; add 0.0620g hydroquinone to the solution under stirring conditions, stir until completely dissolved, measure 167μL of 37% formaldehyde solution, 0.0200g thiourea, and 0.6774g urea respectively, add them to the above solution and stir evenly, and the composite gel reaction solution regulated only by urea is obtained. Take 20mL of the reaction solution sample and seal it in an ampoule bottle, and age it at a constant temperature of 120℃ to generate a composite gel. The gelation time of the reaction solution is 3.5d, and the stability time of the gel sample exceeds 141d. At the 141st day, the sample strength symbol is H. This sample is an organic / inorganic composite gel sample regulated by urea (U) alone, in which the mineralization degree (T) of the inorganic salt is 15×10 4 mg / L, the mass percentage concentration of urea is 1.67%, so the sample symbol is named Composite-T15-U1.67.

[0069] Example 14 further increases the amount of urea on the basis of Example 13, while Comparative Example 4 increases the amount of urea on the basis of Comparative Example 3. Figure 3 The elastic modulus-oscillation frequency relationship curves thereof are given in the results. Under the experimental conditions, the elastic moduli of Comparative Example 4 and Example 14 are 41-57Pa and 69-119Pa, respectively. The results show that the strength of the organic / inorganic composite gel regulated by pure urea increases slightly with increasing urea dosage; the organic / inorganic composite gel regulated by urea-aluminum salt increases significantly, and the elastic modulus of the organic / inorganic composite gel regulated by urea-aluminum salt is much greater than that of the organic / inorganic composite gel regulated by pure urea, indicating that the organic / inorganic composite gel prepared by synergistic regulation of aluminum salt and urea has higher strength and has broad application prospects in the field of deep profile control and water plugging in oil fields.

Claims

1. An organic / inorganic composite gel synergistically regulated by urea and aluminum salt, characterized in that: The invention is prepared from the following composition in percentage by mass: 0.50%-2.00% polymer main agent, 0.05%-0.80% phenol cross-linking agent, 0.05%-0.80% aldehyde cross-linking agent, 0.01%-0.10% deoxidizer, 1.50%-4.00% urea, 0.10%-0.80% aluminum salt, 0.20%-1.20% complexing agent, and the balance is salt water; the polymer main agent is polyacrylamide; The phenolic cross-linking agent is at least one of phenol, resorcinol and hydroquinone; The aldehyde cross-linking agent is at least one of formaldehyde and paraformaldehyde; The deoxidizer is thiourea; The aluminum salt is at least one of aluminum chloride, aluminum nitrate, aluminum sulfate, and aluminum citrate; The complexing agent is at least one of sodium citrate and disodium ethylenediaminetetraacetic acid.

2. The organic / inorganic composite gel according to claim 1, characterized in that: The polyacrylamide comprises at least one of nonionic polyacrylamide, partially hydrolyzed polyacrylamide and acrylamide copolymer; The hydrolysis degree of nonionic polyacrylamide does not exceed 4%, the hydrolysis degree of partially hydrolyzed polyacrylamide does not exceed 25%, and the relative molecular weight of the polymer is 1 million to 5 million.

3. The organic / inorganic composite gel according to claim 1, characterized in that: The salinity of the brine is 15.0×10 4 mg / L, the total concentration of calcium and magnesium ions is 6817.3 mg / L.

4. The organic / inorganic composite gel according to claim 1, characterized in that: The organic component in the composite gel is a gel formed by polyacrylamide and a phenolic crosslinker, and the inorganic components include calcium carbonate particles and magnesium-aluminum layered double hydroxide particles with positively charged layers. The layered double hydroxide and the organic component carboxylate significantly improve the elastic modulus of the composite gel through electrostatic interaction.

5. The organic / inorganic composite gel according to claim 1, characterized in that: The gelling time of the composite gel reaction solution can be adjusted between 1.0 and 14.9 days at 95-120°C.

6. The organic / inorganic composite gel according to claim 1, characterized in that: The stability time of the composite gel at 95-120℃ is more than 135d.

7. The organic / inorganic composite gel according to claim 1, characterized in that: The composite gel is suitable for use as a deep profile control and water plugging agent in high-temperature and high-salinity oil reservoirs.

8. The method for preparing the organic / inorganic composite gel synergistically regulated by urea and aluminum salt according to any one of claims 1 to 7, characterized in that: The following steps are involved: adding the polymer into the saline solution and stirring until completely dissolved to obtain a polymer saline solution; adding aluminum salt and complexing agent into polymer salt solution, stirring until completely dissolved, to obtain polymer salt solution containing aluminum salt; adding a phenolic crosslinking agent to a polymer salt solution containing aluminum salt, and stirring until completely dissolved to obtain a polymer salt solution containing phenolic substances; Continue to add the aldehyde crosslinking agent, deoxidizer and urea to the polymer salt solution containing phenolic substances, stir evenly, and obtain a composite gel reaction solution; The composite gel reaction solution is placed at 95-120° C. for constant temperature aging to obtain a composite gel.

9. The method for preparing the organic / inorganic composite gel synergistically regulated by urea and aluminum salt according to claim 8, characterized in that: When the mass percentage of urea in the reaction system is controlled within the range of 1.50%-4.00% at 95-120°C, the gelling time of the reaction solution can be regulated within the range of 1.0-14.9 days. Increasing the urea concentration in the reaction system can prolong the gelling time of the reaction solution.

10. The method for preparing the organic / inorganic composite gel synergistically regulated by urea and aluminum salt according to claim 8, characterized in that: This preparation method delays the high-temperature cross-linking reaction of polyacrylamide and realizes the comprehensive utilization of minerals in the brine, converting calcium and magnesium ions that destroy the stability of the polymer gel into calcium carbonate and magnesium aluminum layered double hydroxide inorganic particles that enhance the strength and stability of the composite gel, thereby realizing the transformation of unfavorable factors into favorable conditions. This method is a method for in-situ preparation of high-strength organic / inorganic composite gels using polymer brine solutions.

Citation Information

Patent Citations

  • Organic / inorganic crosslinking system plugging agent applicable to high-temperature oil reservoir

    CN102516961A

  • Profile-control and water-plugging agent and profile-control and water-plugging method used for profile control and water plugging of high-temperature and high-salinity oil reservoir

    CN105586024A

  • Single-fluid-method inorganic precipitation type plugging agent as well as preparation method and application thereof

    CN108003855A

  • Profile adjusting and water plugging agent and application, profile adjusting and water plugging system and preparation method and application thereof

    CN108587585A

  • A salt- and high-temperature resistant hydrogel, its preparation method and application

    CN109679604B